RNA Sequencing Reveals That the Genes Related to Cell Cycle and Glycolysis Play an Essential Role in IL-27-Induced Keratinocyte Hyperproliferation - Wu Z; Wang R; Liu Y; Yang B; Wang H (Dove Medical Press, 2024)
Zijun Wu,1,* Ruijing Wang,1,* Yuanjun Liu,1 Bin Yang,2 Huiping Wang1 1Department of Dermatovenereology, Tianjin Medical University General Hospital/Tianjin Institute of Sexually Transmitted Disease, Tianjin, People's Republic of China; 2Department of Burn and Plastic Surgery, General Hospital of Central Theater Command, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Bin Yang, Department of Burn and Plastic Surgery, General Hospital of Central Theater Command, Wuhan, Hubei, People's Republic of China, Email sszxkyb1@163.com Huiping Wang, Department of Dermatovenereology, Tianjin Medical University General Hospital/Tianjin Institute of Sexually Transmitted Disease, Tianjin, People's Republic of China, Email huiping1208@163.comBackground: Psoriasis is characterized by accelerated proliferation of epidermal keratinocytes. IL-27 is relevant to psoriasis pathogenesis. We previously found that IL-27 stimulates the proliferation of keratinocytes. However, the mRNAs involved in the process have not been fully studied. This study aims to identify potential pathways and hub genes associated with proliferation in keratinocytes with IL-27 intervention by bioinformatics analysis.Methods: The mRNA expression profiles from HaCaT cells with or without IL-27 treated were analyzed by bioinformatics tools. The protein-protein interaction (PPI) network was constructed to screen gene clusters and hub genes associated with proliferation. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene Set Enrichment Analysis (GSEA) were used to identify the function of the mRNAs. The GEO database and quantitative real-time PCR (qPCR) were used to verify the expression levels of hub genes in psoriatic skin lesions and IL-27-treated psoriasiform keratinocytes, respectively.Results: We found 1257 differentially expressed genes and screened 2 crucial gene clusters. GO analysis revealed that Cluster 1 was mainly enriched in "Mitotic sister chromatid segregation" and "Spindle". Cluster 2 was mainly enriched in the "Pyruvate metabolic process" and "Oxidoreductase complex". KEGG analysis showed that Cluster 1 and Cluster 2 were mainly enriched in "Cell cycle" and "Glycolysis/Gluconeogenesis", respectively. We then identified 6 hub genes enriched in the two pathways, including CCNB1, PTTG1, CDC20, PLK1, PKM, and LDHA. GSEA complemented the role of the mitochondrial "Oxidative phosphorylation" pathway. Moreover, we found that 6 hub genes were upregulated in psoriasis skin lesions and IL-27 elevated the hub genes expression in M5-induced psoriasiform keratinocytes.Conclusion: IL-27 possibly promotes glycolysis, mitochondrial oxidative phosphorylation, and cell cycle progression in keratinocytes. Additionally, we identified CCNB1, PTTG1, CDC20, PLK1, PKM, and LDHA as hub genes that may be involved in the mechanism of IL-27 facilitating keratinocyte proliferation in psoriasis.Keywords: psoriasis, glycolysis, oxidative phosphorylation, bioinformatics